Role of Minority Populations of Human Immunodeficiency Virus Type 1 in the Evolution of Viral Resistance to Protease Inhibitors - Charpentier, Charlotte (American Society for Microbiology, 2004)
Human immunodeficiency virus type 1 (HIV-1) drug resistance results from the accumulation of mutations in the viral genes targeted by the drugs. These genetic changes, however, are commonly detected and monitored by techniques that only take into account the dominant population of plasma virus. Because HIV-1-infected patients harbor a complex and diverse mixture of virus populations, the mechanisms underlying the emergence and the evolution of resistance are not fully elucidated. Using techniques that allow the quantification of resistance mutations in minority virus species, we have monitored the evolution of resistance in plasma virus populations from patients failing protease inhibitor treatment. Minority populations with distinct resistance genotypes were detected in all patients throughout the evolution of resistance. The emergence of new dominant genotypes followed two possible mechanisms: (i) emergence of a new mutation in a currently dominant genotype and (ii) emergence of a new genotype derived from a minority virus species. In most cases, these population changes were associated with an increase in resistance at the expense of a reduction in replication capacity. Our findings provide a preliminary indication that minority viral species, which evolve independently of the majority virus population, can eventually become dominant populations, thereby serving as a reservoir of diversity and possibly accelerating the development of drug resistance.